A linear packet marking probability function for fast congestion notification (FN) - M. Kadhum, Mohammed; Hassan, Suhaidi (Dr. Sang H. Lee, 2009)
The efficiency of queue management mechanisms depends on how well their control decisions helps in satisfying their objectives regarding congestion avoidance and control. These decisions are implemented and compelled during the design of the packet mark probability and the mark activation functions. If a packet is dropped / marked rather than being allowed to the buffer, a congestion notification is delivered and the congestion avoidance and control carries on to be applied at the router. If the queue management mechanism realizes the need to apply more aggressive congestion control, the recently arrived packet should be dropped to provide early congestion notification. In this paper, we design a new packet drop probability function with a built-in drop activation function for Fast Congestion Notification (FN) mechanism. This design enables the two control decisions, packet admissions and congestion control directing, to be made along with each other. This permits sending congestion avoidance notification as early as required even if the queue is almost empty, and preventing congestion notification even if the queue is almost full but the arrival rate is controllable, thus the buffer is fully utilized and the congestion is detected properly.